Strategy and Effectivity of Sufi Healing as a Therapeutic Process for Curing Diseases - Siti Asiyah; Achmad Lutfi (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2023)
Modern humans experience psychosocial stressors that affect physical and psychological health. This article discusses the strategy and effectiveness of Sufi healing on physical and psychological illnesses as practised at the Rehab Hati Foundation, Cirebon. This study used a phenomenological approach to understand the therapy process and strategy based on Sufi healing. Primary data were obtained from the leaders of the Rehab Hati Foundation, therapists, patients, and guidebooks used by therapists as references in treatment. This study revealed that the Sufi healing-based therapy uses the ruqyah method accompanied by thibbun nabawi (herbal medicine, honey, dates, etc.) and adapted to the disease experienced by the patient and also with spiritual advice. The ruqyah therapy techniques are two kinds, namely ruqyah therapy carried out directly by a therapist, and independent ruqyah therapy carried out by the patient himself or with the help of his family at home.Contribution: This study provides a perspective that the treatment of human illnesses, both physical and psychological, is not only done medically based on medical science. Sufistic therapy, with ruqyah and thibbun Nabawi, can be an alternative to healing human illnesses.